ANALYSIS OF THE QUALITY OF THE SOLD PRODUCT: A CASE STUDY BASED ON SONY CORPORATION - Gulomov Kodir Dilshod ugli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
In this study, we learn the analysis of the quality of product sold. In example cases, Sony Corporation is used as a base. Some main metrics this study focuses on include product durability, customer satisfaction, return rates, and industry benchmarks (performances used to compare companies). Sony’s performance is evaluated with the help of newly shared market research reports, customer reviews, and other financial data in categories of Sony including television, cameras, audio equipment and gaming consoles. This evaluation also examines the role quality management strategies play when brand reputation and sales are concerned.